Jus Primae Noctis in the Medieval Arabic Tradition - Gasimova, Aida (Ancient Near Eastern studies, 2022)
The lord’s right of the first wedding night (jus primae noctis or droit du seigneur) has been a focus for much Western European historiography. The highly celebrated movie Brave Heart (1995), directed and acted by Mel Gibson, drew further attention to the odious privilege of governing classes to deprive ordinary men, particularly those of captive nations, of the right to spend the first wedding night with their brides. There has been much controversy in European scholarship about the origin and peculiarities of such a right and its existence in various medieval European countries. The present paper aims to analyse passages related to the lord’s right of the first wedding night in the medieval Arab sources. Among the classical authors, I consulted mainly ibn Zabālah (d. after 814) in his Akhbār al-Madīna, Abū l-Faraj al-Isfahānī (d. 976) in Kitāb al-aghānī, al-Mas‘ūdī (d. 956) in Murūj al-dhahab, al-Țabarī (d. 923) in Tarik al-rusul wa l-mulūk, an anonymous adab book (tenth century) attributed to al-Jāḥiẓ (d. 868), al-Qazwīnī (d. 1283) in Āthār al-bilād wa akhbār al-‘ibād, Yāqūt al-Rūmī (d. 1229) in Mu‘jam al-buldān, ibn Khaldūn (d. 1406) in Dīwān al-mubtada’ wa l-khabar, and others. My research explores and analyses the main characters and structures of these legends, which require comparative scrutiny with the traditions of neighbouring nations and particularly with the ancient Mesopotamian, Jewish, and Greek texts which appear to be directly related to the custom. I will eventually demonstrate how Arab scholarship, from the decline of the Abbasid Caliphate onwards, has employed age-old legends about woman’s chastity to glorify Arab national dignity and honour.